FIGURATIVE LANGUAGE IN HARRY POTTER AND DEATHLY HALLOWS PART 2 MOVIE - Wiki Tedi Rahmawati; Linda Astuti Rangkuti; Karina Radiyanti (EXCELLENCE: Journal of English and English Education, 2021)
The objectives of the study were to describe the types of figurative language used in Harry Potter and Deathly Hallows Part 2 Movie and to find out the dominant type of the figurative language used in the movie. This study was conducted by applying descriptive qualitative method. The data were collected from Harry Potter and Deathly Hallows Part 2 Movie by analyzing the dialogues spoken by the actors/actress through its text transcribe. The analysis found out there were 6 types of figurative language used, namely simile 28 (28.57%), metaphor 27 (27.55%), hyperbole 20 (20.40%), idiom 13 (13.26%), personification 6 (6.12%), and proverb 4 (4.08%). The most dominant figurative language used was simile.